Metaphors in mathematical instruction effects on high school students' adaptability and representational thinking - Tardecilla, Patrick F.; Joaquin, Ma. Nympha B.; Monterola, Sheryl Lyn C.; De Laza, Crizel Sicat; Rocena, Lady Angela M. (Quezon City College of Education, University of the Philippines Diliman, 2024)
The research investigated how Metaphorical Teaching in Mathematics influences students adaptability and representational thinking. Furthermore, it examined whether adaptability serves as a predictor of representational thinking. Using a sequential mixed-method design, it combined quantitative and qualitative approaches. The quantitative phase involved a two-group pretest-posttest quasi-experimental design with 83 Grade 9 students from a Marikina City public high school. One group was taught using metaphorical teaching, while the other received conventional instruction, both facilitated by the researcher with parallel methods. The qualitative phase included interviews, observations and output examinations to analyze students' experiences.

Quantitative data were gathered using Martin's Adaptability Scale (2017) and a researcher-developed Representational Thinking Test, which was validated by math experts and pilot-tested, demonstrating high reliability. To ensure the comparability of the experimental and control groups before implementing the intervention, a pre-test was administered. A two-tailed independent sample t-test was used to compare the pre-test results between the two groups. Consequently, to determine if there was a significant difference in the posttest mean adaptability scores and representational thinking outcomes between the two classes, a one-tailed independent sample t-test was done. Additionally, to determine whether adaptability is a predictor of representational thinking, a linear regression analysis was carried out using a one-way approach.

The analysis of pretest scores for adaptability and representational thinking showed that both groups were comparable prior to the conduct of intervention. Students exposed to Metaphorical Teaching in Mathematics scored significantly higher in overall adaptability and its sub-aspects, cognitive-behavioral and affective adaptability, than those in the conventional teaching group. Similarly, the experimental group achieved significantly higher scores in representational thinking and its sub-aspects, including communication of information, problem-solving, modeling, and interpretation, excluding presentation of information, where no significant difference was found. These results suggest that using metaphors in mathematics instruction effectively enhances students' adaptability and representational thinking, aiding in better problem-solving, modeling. and interpretation skills. Nevertheless, it was determined that, despite the moderate positive linear relationship, adaptability is not a predictor of representational thinking.

The literature review showed that, although using metaphors in Mathematics is not a new idea, many teachers may lack understanding of how to use them effectively in teaching. Therefore, future research should involve teachers and examine their attitudes toward using metaphors in the classroom. Based on this study's findings, it is recommended to provide teacher training on metaphorical teaching in Mathematics, offering insights into its practical application. Additionally, while this study's metaphors were tailored for Mathematics, it is worth exploring how they connect with students' language skills by examining modern linguistic frameworks that could clarify their role in mathematical instruction.
Thesis
Includes bibliographical references (116-122 leaves)
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Marikina City; Thought and thinking -- Study and teaching (Secondary).; Metaphor; Adaptability (Psychology).